The (non)sense of private equity regulation - Šinka, Michal; Teplý, Petr (Univerzita Pardubice, 2011)
The 2007-2009 global financial turmoil has taught risk managers lessons that will be crucial for developing more stable financial markets in the future. Private equity funds are sometimes believed to have played a major role during this global financial turmoil. In the light of serious economic problems, questions arose whether the regulation of these funds were sufficient or whether the effects of the global crisis would have been mitigated if regulation and supervision had been stricter. In this paper we argue that the private equity regulatory proposals included in the Directive on Alternative Investment Fund Managers in the European Union and the Dodd-Frank at Act in the USA will be inefficient, i.e. the costs of such regulations will outweigh its benefits and will not offer future market protection.
Keywords: private equity; regulation; MAC questions; global crisis; financial markets